2013
DOI: 10.1083/jcb2002oia5
|View full text |Cite
|
Sign up to set email alerts
|

CD98hc (SLC3A2) regulation of skin homeostasis wanes with age

Abstract: Skin aging is linked to reduced epidermal proliferation and general extracellular matrix atrophy. This involves factors such as the cell adhesion receptors integrins and amino acid transporters. CD98hc (SLC3A2), a heterodimeric amino acid transporter, modulates integrin signaling in vitro. We unravel CD98hc functions in vivo in skin. We report that CD98hc invalidation has no appreciable effect on cell adhesion, clearly showing that CD98hc disruption phenocopies neither CD98hc knockdown in cultured keratinocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 65 publications
2
27
0
Order By: Relevance
“…In contrast, crosslinking of CD99 abrogated the increased amino acid influx induced by CD98hc. This result is consistent with the previous report showing that CD98hc-dependent amino acid transport may be involved in modulating CD98-integrin-FAK-RhoA signaling pathway [21]. Taken together, these results suggest that CD98 and CD99 may exert opposite effects on β1 integrin signaling through the regulation of FAK.…”
Section: Cd99 Attenuates Cd98-mediated β1 Integrin Signalingsupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast, crosslinking of CD99 abrogated the increased amino acid influx induced by CD98hc. This result is consistent with the previous report showing that CD98hc-dependent amino acid transport may be involved in modulating CD98-integrin-FAK-RhoA signaling pathway [21]. Taken together, these results suggest that CD98 and CD99 may exert opposite effects on β1 integrin signaling through the regulation of FAK.…”
Section: Cd99 Attenuates Cd98-mediated β1 Integrin Signalingsupporting
confidence: 93%
“…Since a previous study suggested that amino acid transport may regulate CD98hc-mediated β1 integrin signaling by modulating RhoA activation [21], we examined whether crosslinking CD98hc could regulates the Na þ -independent amino acid transport. Crosslinking of CD98hc enhanced influx of L-[ 3 H]-leucine into MCF-7 cells to a certain degree ( Supplementary Fig.…”
Section: Cd99 Attenuates Cd98-mediated β1 Integrin Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…CD98h plays an important role in amino-acid transport by interact with various types of transporter, such as LAT1 and xCT. LAT1 transports large neutral amino acids such as leucine, isoleucine, valine, phenylalanine, tyrosine, tryptophan, methionine, and histidine, while xCT increases intracellular levels of cysteine (7,15,32). In the present study, metabolomic profiles suggested that intracellular amino acid concentrations and GSH were higher in CD98hc-expressing tissues, suggesting that CD98hc is associated with amino acid transport in gastric cancer tissues.…”
Section: Prognostic Role Of Cd98hc and Cd98 Amino Acid Transport In Gmentioning
confidence: 54%
“…K14-CreER T2 , CD98hc fl/fl have been described previously (11). The experiments have been performed on pure FVB/n background mice.…”
Section: Methodsmentioning
confidence: 99%